Pengaruh Ukuran Perusahaan, Umur Perusahaan, Profitabilitas Perusahaan, Solvabilitasperusahaan, Dan Ukuran KAP Terhadap Audit Delay (Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2014) - Wijayanto, Bima Dwi, (Drs. Agus Endro S, M. Si) (2016)
This research purposed to know the influence of company size, the age of company, profitability, solvability, and size of public accountant towards the audit delay (in banking companies which have listed on the Indonesian Stock Exchange from 2012 to 2014). This research examines Banking Company Financial Statements which have listed on the Indonesian Stock Exchange from 2012 to 2014. The data used in this research is secondary data. The population of this research are 43 banking companies which have listed on the Indonesian Stock Exchange from 2012 to 2014. The sample used were 30 banking companies which have listed on the Indonesian Stock Exchange from 2012 to 2014. Analysis of the data used in this study is the classical assumption test and test hypotheses using multiple regression analysis . The results showed the age of company, company size, and the profitability had influence to the audit delay, while solvability and size of public accountant didn't significant influence to the audit delay. Simultaneously, company size, the age of company, profitability, solvability, size public accountant, and auditor's opinion exhibited significantly effect to the audit delay in banking companies which have listed on the Indonesian Stock Exchange from 2012 to 2014.